EXPLORING INNEQUALITY AND CLASS STRUGGLES IN THE ADVENTURES OF HUCKLEBERRY FINN - Hanifah, Cahyarani Triayu; Oktavani, Deliana Fazra; Kamila, Nasywa; Nurholis, Nurholis (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
Mark Twain's The Adventures of Huckleberry Finn serves as a profound critique of the class and racial inequalities entrenched in 19th-century American society. Through the characters of Huck Finn, a poor white boy, and Jim, an escaped slave, Twain illuminates the struggles faced by those at the bottom of the social hierarchy. Jim's journey for freedom symbolizes the broader fight against systemic injustice that characterized his time. As a black man in a society that dehumanizes him, Jim embodies the plight of individuals denied their basic rights and dignity. His aspirations for family, financial stability, and freedom from discrimination reflect a natural right to liberty that society systematically denies him. Huck's moral development is central to the narrative, as he grapples with societal norms that dictate racial superiority and class distinctions. Initially conditioned by the prejudices of his environment, Huck experiences a transformation as he befriends Jim. This relationship challenges his ingrained beliefs and compels him to confront the hypocrisy of a society that claims to be civilized while perpetuating slavery and inequality [5][7]. Huck's internal conflict highlights the tension between societal expectations and personal conscience, ultimately leading him to reject social hierarchies in favor of empathy and human connection. Twain's portrayal of these characters not only critiques institutional racism but also underscores the necessity of personal integrity in the quest for equality. The novel advocates for a moral awakening that transcends class and race, suggesting that true freedom and dignity can only be achieved through compassion and the rejection of oppressive societal constructs [6][8]. In this way, The Adventures of Huckleberry Finn remains a powerful commentary on the enduring issues of inequality and class struggle.